Heterogeneity in Microseismicity and Stress Near Rupture‐Limiting Section Boundaries Along the Late‐Interseismic Alpine Fault. Issue 10 (8th October 2022) - Warren‐Smith, E.; Townend, J.; Chamberlain, C. J.; Boulton, C.; Michailos, K.
Abstract: Paleoseismic evidence from the late‐interseismic Alpine Fault suggests key section boundaries conditionally inhibit rupture. We utilize a year of data from a two‐part seismometer network (Dense Westland Arrays Researching Fault Segmentation) to characterize ∼7, 500 earthquakes (−0.7 ≤ M Lv ≤ 4.2) and ∼800 focal mechanisms, producing high‐resolution structural images of these boundaries to study effects of material and structural heterogeneities on mode‐switching rupture behavior. Lithologically‐controlled frictional behavior and crustal strength appear to influence lateral and vertical on‐fault seismicity distributions. Ultramafic hanging‐wall serpentinite and serpentinite‐related fault core minerals along the South Westland (SW) boundary, result in a locally shallow seismogenic cuttoff (∼8 km) and abundant on‐fault seismicity. Maximum horizontal compressive stress rotations (14° anti‐clockwise and 20° clockwise near the SW and North Westland (NW) boundaries, respectively, relative to the Central Section), coupled with spatially variable fault frictional properties, are more important than geometry alone in controlling Sections' relative frictional stability. Whereas the SW and Central Sections are well‐oriented for failure, the NW Section is severely misoriented compared with favorably oriented faults of the Marlborough Fault Zone, which possibly facilitate a preferred rupture route. Geometrically, a 40° dip change at the SW boundary may be accommodated either by a single through‐going fault plane ‐ a difficult geometry across which to obtain multi‐segment earthquakes when considering rupture dynamics ‐ or by a deeper vertical fault strand truncated by a shallower listric plane. Our new observations have implications for Alpine Fault rupture scenarios and highlight the need to consider a range of spatially heterogeneous, interdependent physical factors when evaluating controls on rupture segmentation. Plain Language Summary: New Zealand's Alpine Fault last ruptured in 1717 AD and the likelihood of it producing a major earthquake in the next 50 years is estimated to be 75%. The magnitude of the next earthquake will be strongly determined by the area of fault rupture. Two key localities along the fault, which correspond to the boundaries between sections of the fault with differing geometry, slip rate and frictional behavior, have been proposed to sometimes, but not always, act as barriers to fault rupture, limiting the sizes of the resulting earthquakes. However, it remains unclear what physical properties control this process. Using seismic data collected from dense seismometer networks, we construct detailed catalogs of small earthquakes occurring near these localities, at Martyr River and Inchbonnie, and precisely map the distribution of active seismicity near the fault. From these data we improve estimates of (a) the subsurface geometry of the fault and how it changes along length, (b) how seismicity is distributed with depth, to understand possible maximum depth of rupture in conjunction with observations of crustal temperatures and structure, and (c) the orientation of the stresses acting on the fault, to understand its stability to tectonic loading and its frictional behavior. Key Points: Dense microseismicity catalogs constrain fault structure, seismogenic depths and the stress field bookending the fault's Central Section On‐fault seismicity, a 40° dip change and a shallow, rheologically controlled cutoff depth are observed at the South Westland boundary Stress analyses indicate South and North Westland Sections are favorably and unfavorably oriented for frictional failure, respectively